Competitiveness and the export performance of the euro area - Filippo di Mauro; Robert Anderton; Ekkehard Ernst; Laurent Maurin; Sonia Pokutova; Wim Melyn; Axel Jochem; N. M. Pakinezou; Javier Torres; Remy Lecat; Mark Cassidy; Roberto Tedeschi; et al. (European Central Bank (ECB), 2005)
Chapter 1 provides an overview and assessment of the price competitiveness and export performance of the euro area and the larger euro area countries, as well as an evaluation of how standard equations have been able to explain actual export developments. Chapter 2 carries out a constant market share analysis for the euro area and thereby sheds light on the reasons for movements in aggregate export market shares by looking at the sectoral and geographical composition of euro area exports. Chapter 3 looks at the evolution of the technological competitiveness of the euro area and major competitors – proxied by patenting activity and R&D expenditure – and analyses some structural indicators of competitiveness using survey data. Chapter 4 then looks at the impact of FDI on competitiveness and export performance. Finally, Chapter 5 summarises the main findings of the report, but also critically evaluates their importance and implications.
Keywords: 330; Internationaler Wettbewerb; Eurozone; EU-Staaten